Mn-for-Fe substitution in Fe1-xMnxIn2S4 thiospinel – Crystal structure and thermoelectric properties. (May 2021) - Wyżga, Paweł; Veremchuk, Igor; Koželj, Primož; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract: Crystal structure as well as magnetic and thermoelectric properties of the quaternary Fe1- x Mn x In2 S4 thiospinel were investigated. A complete homogeneity range between FeIn2 S4 and MnIn2 S4 was confirmed by powder X-ray diffraction phase analysis supported by a linear increase of the cubic unit-cell parameter for greater Mn content, obeying Vegard's law. Rietveld refinement revealed a gradual decrease of the inversion parameter i upon incorporation of Mn into the structure, which indicated a change from inverse spinel (for FeIn2 S4 ) to nearly-normal spinel (for MnIn2 S4 ). This quaternary compound is an n -type semiconductor with high electrical resistivity ρ  > 5 × 10 −4  Ω m and Seebeck coefficient | α | > 250 μV K −1 above RT. The thermal conductivity followed a compositional dependence typical for solid solutions and thus revealed a minimum for samples with 0.4 <  x  ≤ 0.8. The power factor and thermoelectric figure of merit monotonously decreased for greater Mn content within the quaternary compound. All samples showed magnetic transitions below 12 K with antiferromagnetic interactions. The determined effective magnetic moments corresponded to values for Fe 2+ and Mn 2+ ions. Graphical abstract: Image 1 Highlights: Quaternary Fe1- x Mn x In2 S4 thiospinels ( x  = 0.2, 0.4, 0.6, 0.8, 1) were synthesized. A continuous homogeneity range between FeIn2 S4 and MnIn2 S4 was confirmed. Spinel crystal structure changed from inverse to nearly-normal upon increasing x. High electrical resistivity limited the power factor PF  < 1.7 × 10 −4  W m −1 K −1 . Thermal conductivity revealed a trend typical for solid solutions.